(untitled) (Fiep Bulletin - online, 2012)
In term of 29th and 31st of August 2007 was held in Bratislava 4th FIEP European Congress“Physical Education and Sports – Teachers’ Preparation and Their Employability inEurope”. The congress was organized by the Faculty of Physical Education and Sport ofComenius University, Slovak Scientific Society for Physical Education and Sports and byInternational Federation of Physical Education (FIEP). Congress was significantly supported byMinistry of Education of the Slovak Republic, Slovak Olympic Committee, and SlovakParalympic Committee as well as by another business subjects like General credit bank joint-stockcompany.The aim of the congress brought a new knowledge about P.E. teachers’ preparation inEurope, as well as knowledge about curriculum changes based on Bologna Declaration, educationalnotification and labour market and employability the highly educated specialists and experts in thefield of sport in Europe, problems and perspectives of P.E. educational process in schools andknowledge about selection of sport gifted youth.